The role of elastic restoring forces in right-ventricular filling - Pérez Del Villar, Candelas (Cardiovasc Res, 2015)
AIMS: The physiological determinants of RV diastolic function remain poorly understood. We aimed to quantify the contribution of elastic recoil to RV filling and determine its sensitivity to interventricular interaction. METHODS AND RESULTS: High-fidelity pressure–volume loops and simultaneous 3-dimensional ultrasound sequences were obtained in 13 pigs undergoing inotropic modulation, volume overload, and acute pressure overload induced by endotoxin infusion. Using a validated method, we isolated elastic restoring forces from ongoing relaxation using conventional pressure–volume data. The RV contracted below the equilibrium volume in >75% of the data sets. Consequently, elastic recoil generated strong sub-atmospheric passive pressure at the onset of diastole [−3 (−4 to −2) mmHg at baseline]. Stronger restoring suction pressure was related to a shorter isovolumic relaxation period, a higher rapid filling fraction, and lower atrial pressures (all P < 0.05). Restoring forces were mostly determined by the position of operating volumes around the equilibrium volume. By this mechanism, the negative inotropic effect of beta-blockade reduced and sometimes abolished restoring forces. During acute pressure overload, restoring forces initially decreased, but recovered at advanced stages. This biphasic response was related to alterations of septal curvature induced by changes in the diastolic LV–RV pressure balance. The constant of elastic recoil was closely related to the constant of passive stiffness (R = 0.69). CONCLUSION: The RV works as a suction pump, exploiting contraction energy to facilitate filling by means of strong elastic recoil. Restoring forces are influenced by the inotropic state and RV conformational changes mediated by direct ventricular interdependence.